PEMISAHAN DAN ANALISIS 137Cs DARI LARUTAN PELAT ELEMEN BAKAR U-7%Mo/Al - Anggraini, Dian; Noviarty, Noviarty; Yanlinastuti, Yanlinastuti; Ginting, Aslina Br.; Kriswarini, Rosika; Nugroho, Arif; Boybul, Boybul (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The aim of this research is to get a valid method of separating cesium from U-7Mo/Al fuel plate solution through determination of parameter of method (accuracy, precision, and recovery). Precipitation method and cation exchange method that are used refer to standard ASTM 690-000 and research result of U3Si2/Al. Parameter method determination has been done by using 150 μL sample (U-7%Mo/Al fuel plate solution, 50 μL of standard solution in 2 mL of HCl 0,1 N. The sample solution was undergone precipitation process by using HClO4 concentrated and 225 mg of CsNO3 as carrier in temperature 0oC for an hour, while exchange cation process was done by using 400 mg of resin zeolite Lampung. The analysis of 137Cs in CsClO4 and 137Cs - zeolite was done by gamma spectrometer. Determination of recovery method was done by comparing count value of 137Cs before and after separation process. Recovery of precipitation method was obtained 95.56 % with accuracy and precision measurement of 0.375 % and 1.875 % respectively, while recovery of cation exchange method obtained 26.73 %. To sum up, the results show that precipitation method better than exchange cation method for separation 137Cs from U-7Mo/Al fuel plate solution.